IMPLEMENTATION OF THE SMART METHODS (SIMPLE MULTI-ATTRIBUTE RATING TECHNIQUE) FOR LOCATION SELECTION OF INDUSTRIAL WORK PRACTICE AND MONITORING IN VOCATIONAL SCHOOL STUDENTS - Aulia Rizky Muhammad Hendrik Noor Asegaff; M Dedy Rosyadi; Budi Ramadhani (Fakultas Teknik Universitas Lambung Mangkurat, 2022)
Industrial Work Practices are educational, training, and learning activities for SMK (Vocational High School) students in the business world or the industrial world related to student competencies according to the fields they are involved. However, several problems arise in practice, such as difficulty updating data and distribution of random locations. It is deemed unfair for students because some get locations far from where they live. There is no forum for monitoring the development of internships by supervisors for students, both in reports from daily and final reports. So we need an information system that can provide solutions to these problems. Making internship activities more effective and efficient for Schools, Guiding Teachers, Students and Prakerin Partners. The SMART (Simple Multi-Attribute Rating Technique) method supports decision-makers in choosing between several alternatives.